Familial adenomatous polyposis with early onset dysplasia in a Bangladeshi girl: a case report - Nahid, Khan Lamia; Md Rukunuzzaman, -; Khadga, Mukesh; Begum, Fahmida; Karim, ASM Bazlul (Bangladesh Journal of Child Health, 2020)
Familial adenomatous polyposis (FAP) is characterized by hundreds to thousands of adenomatous polyps in the colon which usually starts at adolescence. Familial adenomatous polyposis (FAP) is a rare, autosomal dominant condition caused by a defect in the adenomatous polyposis coli (APC) gene. FAP arises from germline mutations of the APC gene on chromosome 5q21. If left untreated, all patients will develop colon cancer by age 35-40 years. Their lifetime risk of developing colorectal cancer is estimated to exceed 99% in patients who do not undergo a colectomy. Eventually, there is increased risk of development of other malignancies. Early surgical removal of colon can greatly reduce the spread of cancer. We reported a case of FAP whose symptoms started at early age. Early dysplastic changes were found on histological report. She had undergone prophylactic colectomy. Though appropriate timing for colectomy is late teens, she had surgery much earlier time. Ileal pouch anal anastomosis was done instead of Ileorectal anastomosis. Large sized polyps were the indication of preponed colectomy. But lifelong surveillance is necessary for the girl to detect other malignancies after colectomy Bangladesh J Child Health 2019; VOL 43 (3) :179-182